PROXIMATE LOCAL FOOD WASTE IN ALTERNATIVE FISH FEED PRODUCTION IN SOUTHEAST MALUKU - Cenny Putnarubun; Maria Ngamelubun; Daniel Ngabalin; Jakomina Metungun (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2023)
Utilization of local food waste as an innovation in diversifying quality fish feed products in producing superior seeds. The study aimed to determine the nutritional content of local food waste. The research was carried out for 2 months,. The pr,imate analysis method (AOAC, 2005) and the results are presented in table and descriptive form. The research was conducted in two stages, namely 1). Local food waste sampling stage and 2) proximate analysis stage. The results obtained are proximate coconut cake which includes protein content: 7.29%, fat: 38.76%, water content: 3.05%, ash content: 22.247% and crude fiber: 24.29%. The proximate content of cassava leaves includes: protein content: 22.53%, fat: 5.05%, water content: 5.1%, ash content: 22.75%, and crude fiber: 33.46%, nutritional content of Moringa leaves among others: protein content: 25.66%, fat: 2.54%, water content: 7.4%, ash content: 22.247%, and crude fiber: 30.01%. The results show that local food staples still have a high enough nutritional content so that they can be used as raw materials for fish feed.